2023
DOI: 10.1177/03635465231157758
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Adverse Events and Complications After Isolated Posterior Medial Meniscus Root Repairs

Abstract: Background: Medial meniscus posterior root (MMPR) tears are recognized as a substantial cause of disability and morbidity. However, meniscus root repair, regardless of technique, is not without potential complications. Purpose: To evaluate the reported incidence of complications and adverse events after isolated MMPR repair. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The MM posterior root (MMPR) plays a crucial role in maintaining the meniscus's normal function by controlling its movement. A tear in the MMPR (MMPRT) can cause abnormal loading and movement of the meniscus, leading to accelerated articular cartilage degeneration in the knee joint [1,2]. MMPRTs are a significant concern in orthopaedic practice as they are associated with a range of functional impairments and pain.…”
Section: Introductionmentioning
confidence: 99%
“…The MM posterior root (MMPR) plays a crucial role in maintaining the meniscus's normal function by controlling its movement. A tear in the MMPR (MMPRT) can cause abnormal loading and movement of the meniscus, leading to accelerated articular cartilage degeneration in the knee joint [1,2]. MMPRTs are a significant concern in orthopaedic practice as they are associated with a range of functional impairments and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, MMPR repair is being performed more frequently. However, MMPR repair does not completely prevent the progression of osteoarthritic changes [ 6 , 7 ]. Moreover, it has been reported that there is a correlation between the MM extrusion (MME) progression and the narrowing of the medial joint space [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term outcomes of nonoperative management of medial meniscus (MM) posterior root (MMPR) tears (MMPRTs) are reported to be poor [18]; however, the mid-term to long-term outcomes of MMPR repair have known to be favourable [2,5,17]. Regardless, MMPR repair does not completely prevent the progression of osteoarthritis and medial joint space (MJS) narrowing [2,8,14]. While many similar studies have reported on postoperative MM extrusion (MME) progression [19,23,29], a previous study reported that MMPR repair slowed the progression of osteoarthritis compared with conservative treatment or meniscectomy in a rabbit model [3].…”
Section: Introductionmentioning
confidence: 99%